A hybrid multi-objective improved bacteria foraging algorithm for economic load dispatch considering emission. (2015) - Pandi, V. Ravikumar; Mohapatra, Ankita; Panigrahi, B.K.; Krishnanand, K.R.
In this paper, a hybrid multiobjective improved bacterial foraging algorithm with fuzzy dominance sorting (FSIBF) is proposed and used to solve environmental friendly economic load dispatch problem. The fuzzy dominance-based sorting procedure is used to select the non-dominated solutions in the Pareto front. The proposed algorithm is applied to nonlinear constrained multiobjective environmental friendly economic load dispatch problem. In the proposed work, we have considered the standard IEEE 30-bus six-generator test system with fuel cost and emission as two conflicting objectives to be optimised simultaneously satisfying the system's operational constraints. The constraints imposed from the operation point of view are the limits on generator real power and reactive power outputs, bus voltages and power flow in the transmission lines. The proposed work also includes the effect of having non-smooth cost characteristics of the thermal generators which arises because of the valve point loading effect. The practical generator constraints such as ramp rate limits and prohibited operating zones are also incorporated in this work suitably.